2019
DOI: 10.1111/aji.13115
|View full text |Cite
|
Sign up to set email alerts
|

Poly(I:C) alters placental and fetal brain amino acid transport in a rat model of maternal immune activation

Abstract: Problem Maternal immune activation (MIA) during pregnancy is associated with increased chances of neurodevelopmental disorders including schizophrenia and autism spectrum disorder (ASD). However, the exact mechanism through which MIA contributes to altered neurodevelopment is unknown. Due to the important role that amino acids play in neurodevelopment, altered amino acid transport could play a role in neurodevelopmental disorders. Indeed, altered plasma concentrations of multiple amino acids have been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 64 publications
10
38
1
Order By: Relevance
“…A potential mechanism behind altered transporter expression may stem from cytokine-mediated pathways. Poly I:C induced the expression of pro-inflammatory cytokines in the serum [17] and kidneys of pregnant rats. Indeed, numerous studies have demonstrated poly I:C-mediated induction of pro-inflammatory cytokines both in vivo in the liver, placenta, and brain [15,36,37] and in vitro [38][39][40].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A potential mechanism behind altered transporter expression may stem from cytokine-mediated pathways. Poly I:C induced the expression of pro-inflammatory cytokines in the serum [17] and kidneys of pregnant rats. Indeed, numerous studies have demonstrated poly I:C-mediated induction of pro-inflammatory cytokines both in vivo in the liver, placenta, and brain [15,36,37] and in vitro [38][39][40].…”
Section: Discussionmentioning
confidence: 96%
“…As compared to saline controls, the mRNA expression of IL-6, IL-1β, and TNF-α in the kidneys was significantly higher in the poly I:C-treated groups at 6 and 24 h. While the levels of IL-1β and TNF-α returned to baseline at 48 h, levels of IL-6 remained significantly higher at 48 h in the poly I:Ctreated group (Figure 1). Maternal serum concentrations of IL-6 were elevated by approximately 16fold at 6 h after poly I:C administration (p < 0.05) and returned to baseline by 24 h, as determined by ELISA [17].…”
Section: Effect Of Poly I:c On the Mrna Expression Of Renal Drug Tranmentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, mice lacking these transmembrane proteins are protected from PolyI:C-induced placental maldevelopment and embryonic loss, implicating placental maldevelopment as a critical determinant causing adverse pregnancy outcomes during viral inflammation (18). In rats, PolyI:C administration at midgestation is associated with altered expression of amino acid and drug transporters in the placenta, resulting in a corresponding change in amino acid concentrations in the fetus (48,49). Term human placental explants also exhibit altered expression and function of multidrug resistance transporters following challenge with PolyI:C (50).…”
Section: Discussionmentioning
confidence: 99%
“…Other changes reported for the placenta after exposure to MIA include a decrease in placenta weight (36). Furthermore, upregulation of certain amino acids transporters was reported (42), potentially leading to nutritional changes of the fetus. Damage or irreversible changes to the placenta caused by MIA could affect outcomes in the offspring.…”
Section: Placenta and Body Weightmentioning
confidence: 98%